Type 2 Diabetes Modifies Skeletal Muscle Gene Expression Response to Gastric Bypass Surgery - Barberio, Matthew D.; Dohm, G. Lynis; Pories, Walter J.; Gadaleta, Natalie A.; Houmard, Joseph A.; Nadler, Evan P.; Hubal, Monica J. (Frontiers in Endocrinology, 2021)
Roux-en-Y gastric bypass (RYGB) is an effective treatment for type 2 diabetes mellitus (T2DM) which can result in remission of clinical symptoms, yet mechanisms for improved skeletal muscle health are poorly understood. We sought to define the impact of existing T2DM on RYGB-induced muscle transcriptome changes. Methods: Vastus lateralis biopsy transcriptomes were generated pre- and 1-yr post-RYGB in adult Black American females with (T2D; n = 5, age=51±6 yr, BMI=53.0±5.8 kg/m2) and without (CON; n = 7,43±6 yr,51.0±9.2 kg/m2) T2DM via Affymetrix microarrays. Insulin, glucose, and HOMA-IR were measured in blood at the same time points. ANCOVA detected differentially expressed genes (p< 0.01, fold change > |1.2|), which were used to identify enriched biological pathways. Results: Pre-RYGB, 95 gene probes were downregulated with T2D including subunits of mitochondrial complex I. Functional analysis of differentially regulated genes Pre-RYGB identified Mitochondrial Dysfunction” (p = 1.66 x 10-11), “Oxidative Phosphorylation” (p =4.45 x 10-11), Post-RYGB, the T2D group had normalized gene expression when compared to their non-diabetic counterparts with only 3 genes remaining significantly different. Functional analysis of differentially reugaled genes in T2D pre-to-post RYGB identified Oxidative Phosphorylation (5.19 x 10-8), Mitochondrial Dysfunction (1.15 x 10-6), Conclusion: Black American females with T2DM show extensive down regulation of genes across aerobic metabolism pathways prior to RYGB, which resolves 1-year post-RYGB and is related to improvements in clinical markers. These data support efficacy of RYGB for improving skeletal muscle health, especially in patients with T2DM.